Rancang Bangun Jaringan Internet dengan Memperhatikan Etika Profesi TI Menggunakan Web Filtering Pada Router Mikrotik 951G-2HND - Lutvi Riyandari; Joko Purnomo (LPPM STMIK Widya Utama, 2020)
Computer network technology as a medium of data communication nowadays has been increasing. With the higher level of demand and the increasing number of network users want a form of network that can provide maximum results both in terms of efficiency and increased network security itself. Research conducted in Vocational High School in Banyumas, in this study the method used to build a computer network using Network Development Lifecycle model (NDLC). Is the design of internet network using Router Mikrotik 951G-2HnD as web filtering at Vocational High School in Banyumas its performance refers to attribute Dimension of Quality for Goods? After the network was built and implemented, researcher tested the system with two tests: product test and benefit test, taking sample of respondents for product test ie 5 computer network experts and 40 from internet users at Vocational High School for benefit test. After a successful statistical test with a score above the product test value determined that is 75 % and the result is 86,66 %. The benefit test score is also above the predefined benefit test score of 75 % and the result of the benefit test is 99,37 %. Keywords─ NDLC,Router Mikrotik 951G-2HnD , Product test, Benefit test.